2016
DOI: 10.1016/j.celrep.2016.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibition of β-Secretase Processing of the Alzheimer Disease Amyloid Precursor Protein

Abstract: Development of disease-modifying therapeutics is urgently needed for treating Alzheimer disease (AD). AD is characterized by toxic β-amyloid (Aβ) peptides produced by β- and γ-secretase-mediated cleavage of the amyloid precursor protein (APP). β-secretase inhibitors reduce Aβ levels, but mechanism-based side effects arise because they also inhibit β-cleavage of non-amyloid substrates like Neuregulin. We report that β-secretase has a higher affinity for Neuregulin than it does for APP. Kinetic studies demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 69 publications
3
89
0
Order By: Relevance
“…Therefore, depending on the substrates’ localization, some BACE1 substrates are predominantly cleaved in endosomes, whereas others are mostly cleaved in the TGN. These different cellular localizations of BACE1 activity are even exploited for the development of substrate‐specific BACE1 inhibitors, which selectively target BACE1 in endosomes (Rajendran et al , ; Mitterreiter et al , ; Ben Halima et al , ). On the other hand, partly due to lack of suitable reagents, the exact cleavage compartment—assumed to be late in the secretory pathway or at the plasma membrane—has been identified for only few substrates of ADAM10.…”
Section: Cellular Localization Of Ectodomain Sheddingmentioning
confidence: 99%
“…Therefore, depending on the substrates’ localization, some BACE1 substrates are predominantly cleaved in endosomes, whereas others are mostly cleaved in the TGN. These different cellular localizations of BACE1 activity are even exploited for the development of substrate‐specific BACE1 inhibitors, which selectively target BACE1 in endosomes (Rajendran et al , ; Mitterreiter et al , ; Ben Halima et al , ). On the other hand, partly due to lack of suitable reagents, the exact cleavage compartment—assumed to be late in the secretory pathway or at the plasma membrane—has been identified for only few substrates of ADAM10.…”
Section: Cellular Localization Of Ectodomain Sheddingmentioning
confidence: 99%
“…These alarming effects can be better explained by exploring the molecular mechanism through which BACE1 processes the amyloidogenic substrate APP. It was reported that BACE1 is not entirely selective toward targeting solely the amyloidogenic substrate, in fact, it was even noticed that BACE1 has a greater affinity toward the cleavage of the nonamyloidogenic substrates like neuregulin‐1 (NRG1) . NRG1 has various vital roles in developmental processes, among which is neuronal myelination, in addition, BACE1 is needed to activate NRG1 .…”
Section: Failure Of Bace1 Inhibitors: Lessons To the Futurementioning
confidence: 99%
“…Hence, BACE1 inhibitor will not only abolish BACE1 role in processing APP, which is needed to tackle AD, but it will also prevent the cleavage of the nonamyloid substrates that are required for their function. At the molecular level, it was established that the cleavage of APP by BACE1 happens in an early endosome, where both the substrate and the enzyme undergo endocytosis . On the other hand, it was reported that BACE1 processing of the nonamyloidogenic substrates is not endocytosis‐dependent .…”
Section: Failure Of Bace1 Inhibitors: Lessons To the Futurementioning
confidence: 99%
“…In monkeys, BACE1 inhibition decreased sAPP␤ and A␤ in cerebrospinal fluid (CSF) and increased sAPP␣ as measured by ELISA, but there was no change in labeled sAPP␣ kinetics, suggesting that BACE1 inhibition may not boost ␣-secretase processing of APP to the same degree (11). In human induced pluripotent stem cell-derived neurons, inhibition of BACE1 reduced sAPP␤ and A␤ and reciprocally increased sAPP␣ (12), whereas inhibition of ␥-secretase resulted in an increase in sAPP␣ and a decrease in sAPP␤ (9). This latter result suggests a level of feedback within the ADAM10-␥-secretase complex (9).…”
Section: The Canonical ␣- ␤- and ␥-Secretases And App Fragmentsmentioning
confidence: 99%